Identification of Conserved Epitopes in SARS-CoV-2 Spike and Nucleocapsid Protein - Forcelloni, Sergio; Benedetti, Anna; Dilucca, Maddalena; Giansanti, Andrea (Current Genomics, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel virus that first occurred in Wuhan in December 2019. The spike glycoproteins and nucleocapsid proteins are the most common targets for the development of vaccines and antiviral drugs. Objective: We herein analyze the rate of evolution along with the sequences of spike and nucleocapsid proteins in relation to the spatial locations of their epitopes, previously suggested to contribute to the immune response caused by SARS-CoV-2 infections. Methods: We compare homologous proteins of seven human coronaviruses: HCoV-229E, HCoV- -OC43, SARS-CoV, HCoV-NL63, HCoV-HKU1, MERS-CoV, and SARS-CoV-2. We then focus on the local, structural order-disorder propensity of the protein regions where the SARS-CoV-2 epitopes are located. Results: We show that most of nucleocapsid protein epitopes overlap the RNA-binding and dimerization domains, and some of them are characterized by a low rate of evolutions. Similarly, spike protein epitopes are preferentially located in regions that are predicted to be ordered and wellconserved, in correspondence of the heptad repeats 1 and 2. Interestingly, both the receptor-binding motif to ACE2 and the fusion peptide of spike protein are characterized by a high rate of evolution. Conclusion: Our results provide evidence for conserved epitopes that might help develop broad- -spectrum SARS-CoV-2 vaccines.
Keywords: conserved epitopes